Zum neutralen, verhüllenden und dysphemistischen Sprachgebrauch in deutschsprachigen Traueranzeigen - Agnieszka Gaweł (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
The communication about death is determined by numerous social constraints, resulting from the fear of the confrontation with this inevitable experience, as well as the sacralisation of the sphere of dying in the European culture. In this paper we analyse the influence of the social convention on the language use in German obituaries. The focus of the analysis lies on the typology of designations of death, as well as various forms of neutral, euphemistic and dysphemistic notification of decease.